Optical tweezers and their applications. (October 2018) - Polimeno, Paolo; Magazzù, Alessandro; Iatì, Maria Antonia; Patti, Francesco; Saija, Rosalba; Esposti Boschi, Cristian Degli; Donato, Maria Grazia; Gucciardi, Pietro G.; Jones, Philip H.; Volpe, Giovanni; Maragò, Onofrio M.
Highlights: We review optical tweezers and their applications. T-matrix methods for calculations of optical forces. Overview of typical optical tweezers calibration methods. Applications in biology, nanotechnology, spectroscopy, stochastic thermodynamics, critical Casimir forces, and active matter. Abstract: Optical tweezers, tools based on strongly focused light, enable optical trapping, manipulation, and characterisation of a wide range of microscopic and nanoscopic materials. In the limiting cases of spherical particles either much smaller or much larger than the trapping wavelength, the force in optical tweezers separates into a conservative gradient force, which is proportional to the light intensity gradient and responsible for trapping, and a non-conservative scattering force, which is proportional to the light intensity and is generally detrimental for trapping, but fundamental for optical manipulation and laser cooling. For non-spherical particles or at intermediate (meso)scales, the situation is more complex and this traditional identification of gradient and scattering force is more elusive. Moreover, shape and composition can have dramatic consequences for optically trapped particle dynamics. Here, after an introduction to the theory and practice of optical forces with a focus on the role of shape and composition, we give an overview of some recent applications to biology, nanotechnology, spectroscopy, stochastic thermodynamics, critical Casimir forces, and active matter.